(untitled) (Research, Society and Development, 2020)
Tuberculosis is caused by Mycobacterium tuberculosis and is associated with several health determinants, such as: low income, uncontrolled urbanization and the disruption of health services. The objective of this study was to carry out an epidemiological analysis of the tuberculosis situation among the indigenous population of the northern region of Brazil from 2015 to 2019. Documentary research of a quantitative nature using the statistical method. The study population was composed of indigenous people of the various ethnicities residing in the northern region of the country, who had tuberculosis and were notified in the SINAN information system. The data sources were from the SUS / DATASUS Hospital Information System, from January 1, 2015 to December 31, 2019. The data were presented in tables and analyzed based on the available literature. The results analyzed in the period showed that, in the northern region, the state of Amazonas contributed more than 50% of cases of tuberculosis among indigenous peoples, young adults aged 15 to 44 years represent 47.1% of cases and 0 to 14 years and 65 years or more total 34.6%. Regarding the situation of cure and abandonment of treatment in the North, it represents, respectively, 63.9% and 6.6%. We conclude that there are weaknesses in the diagnosis and timely treatment of these populations as they are remote areas, which require new strategies for accessibility and guarantee of primary care.